YAPPA MAWINE TRADITION AS A MIRROR OF THE TIMES IN THE NOVEL THE WOMAN CRYING TO THE BLACK MOON - Afandi, Iswan; Juanda, Juanda (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
This study analyzes the novel "Perempuan yang Menangis pada Bulan Hitam" by Dian Purnomo using Alan Swingewood's sociology of literature theory. The purpose of this study is to explore how this novel reflects the socio-cultural conditions of the Sumbanese people, particularly in the context of the Yappa Mawine (catch marriage) tradition, as well as to examine authorship and literary production. The research method used is a qualitative approach with content analysis techniques, assisted by the Nvivo application. The results show that this novel functions as a social document that reflects the norms and traditions of Sumbanese society and illustrates the social tensions that arise from the conflict between traditional values and modernity. This research has implications for a deeper understanding of the role of literature in reflecting and influencing social change, as well as expanding the application of Swingewood's literary sociology theory to contemporary Indonesian literary works.